Registration of Marriage in Positive Law: Analysis of Justice for Women and Islamic Jurisprudence (Fiqh) - Sari, Widya; Arif, Muhammad (Madania: Jurnal Kajian Keislaman, 2025)
This study aims to analyze the provisions of the Indonesian Marriage Law and the Compilation of Islamic Law concerning the registration of marriage as a mechanism for the protection of women. The study employs a women’s justice perspective by integrating feminist theory and Islamic jurisprudence (fiqh). Through a feminist approach, this research identifies scholarly perspectives that emphasize the importance of marriage registration in ensuring legal protection and justice for women. This research offers an integrative analysis of women’s justice and fiqh, underscoring the importance of marriage registration as a legal guarantee for women. This study adopts a library-based research design, with data analyzed through content analysis. The findings indicate that marriage registration, from the perspective of women’s justice, is not merely an administrative requirement but a crucial legal element that determines the legal recognition of marriage and prevents harm to women, particularly in cases of unregistered marriage. From the perspective of fiqh, marriage registration can be understood as a contemporary form of marriage declaration without introducing additional essential pillars of marriage. In this context, marriage registration may be integrated with the requirement of witnesses, where witnesses function not only as living witnesses but also as witnesses to the deed. Such witnesses ultimately serve as authentic legal evidence of marriage. Based on the combined analysis of women’s justice and fiqh, this study proposes a revision of Article 2 of the Marriage Law and an amendment to Article 24 concerning marriage witnesses in the Compilation of Islamic Law in Indonesia. Penelitian ini bertujuan untuk menganalisis ketentuan dalam Undang-Undang Perkawinan dan Kompilasi Hukum Islam terkait pencatatan perkawinan sebagai mekanisme perlindungan terhadap perempuan. Penelitian ini menggunakan perspektif keadilan perempuan dengan mengintegrasikan teori feminis dan hukum Islam (fikih). Melalui pendekatan feminis, penelitian ini mengkaji pandangan para sarjana yang menekankan pentingnya pencatatan perkawinan dalam menjamin perlindungan hukum dan keadilan bagi perempuan. Penelitian ini menawarkan analisis integratif antara keadilan perempuan dan fikh yang menegaskan pencatatan perkawinan sebagai jaminan hukum bagi perempuan. Penelitian ini menggunakan desain penelitian kepustakaan dengan analisis data melalui metode analisis isi. Hasil penelitian menunjukkan bahwa pencatatan perkawinan, dari perspektif keadilan perempuan, bukan sekadar persyaratan administratif, melainkan unsur hukum yang krusial dalam menentukan pengakuan hukum terhadap perkawinan serta mencegah terjadinya kemudaratan bagi perempuan, khususnya dalam kasus perkawinan tidak tercatat. Dari perspektif fikih, pencatatan perkawinan dapat dipahami sebagai bentuk kontemporer dari pengumuman perkawinan (i‘lān al-nikāḥ) tanpa menambahkan rukun esensial baru dalam perkawinan. Dalam konteks ini, pencatatan perkawinan dapat diintegrasikan dengan ketentuan saksi, di mana saksi tidak hanya berfungsi sebagai saksi hidup, tetapi juga sebagai saksi akta. Saksi akta tersebut pada akhirnya berfungsi sebagai alat bukti hukum autentik atas suatu perkawinan. Berdasarkan analisis keadilan perempuan dan fikih, penelitian ini mengusulkan revisi Pasal 2 Undang-Undang Perkawinan serta perubahan Pasal 24 Kompilasi Hukum Islam terkait ketentuan saksi perkawinan di Indonesia.